B-1 cells in immunotoxicology: Mechanisms underlying their response to chemicals and particles - Hiéronimus, Léa; Huaux, François (Frontiers in Toxicology, 2023)
Since their discovery nearly 40 years ago, B-1 cells have continued to challenge the boundaries between innate and adaptive immunity, as well as myeloid and lymphoid functions. This B-cell subset ensures early immunity in neonates before the development of conventional B (B-2) cells and respond to immune injuries throughout life. B-1 cells are multifaceted and serve as natural- and induced-antibody-producing cells, phagocytic cells, antigen-presenting cells, and anti-/pro-inflammatory cytokine-releasing cells. This review retraces the origin of B-1 cells and their different roles in homeostatic and infectious conditions before focusing on pollutants comprising contact-sensitivity-inducing chemicals, endocrine disruptors, aryl hydrocarbon receptor (AHR) ligands, and reactive particles.